2020
DOI: 10.38157/business-perspective-review.v2i2.122
|View full text |Cite
|
Sign up to set email alerts
|

HR Professionals’ Intention to Adopt and Use of Artificial Intelligence in Recruiting Talents

Abstract: Purpose: The present study is an attempt to explore the antecedents of behavioral intention to use artificial intelligence (AI) in recruiting talents by the HR professionals in Bangladesh. Drawing on the principle of the unified theory of acceptance and use of technology (UTAUT), which was built on the premise of technology acceptance model, the theory of planned behavior, the theory of reasoned action, and so forth, the current study has been conducted in the context of Bangladesh. Method: Building on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…Similarly, AI-based tools from the context of organizational and industrial psychology, e.g., to facilitate personnel selection, are becoming increasingly popular. However, because perceived ease of use and perceived usefulness could explain only 12% of the variance in attitude towards AI, other variables seem to be important in determining a person's attitude towards AI technology, e.g., anxiety (e.g., Kim, 2017), perceived trustworthiness (e.g., Nadarzynski et al, 2019), availability (e.g., Alam et al, 2020), or techsavviness (e.g., Pinto dos Santos et al, 2019. Nevertheless, even if predictors of attitude towards AI remain to a large extent unclear, attitude predicts intention to use AI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, AI-based tools from the context of organizational and industrial psychology, e.g., to facilitate personnel selection, are becoming increasingly popular. However, because perceived ease of use and perceived usefulness could explain only 12% of the variance in attitude towards AI, other variables seem to be important in determining a person's attitude towards AI technology, e.g., anxiety (e.g., Kim, 2017), perceived trustworthiness (e.g., Nadarzynski et al, 2019), availability (e.g., Alam et al, 2020), or techsavviness (e.g., Pinto dos Santos et al, 2019. Nevertheless, even if predictors of attitude towards AI remain to a large extent unclear, attitude predicts intention to use AI.…”
Section: Discussionmentioning
confidence: 99%
“…Both Dwivedi et al (2019) and Khechine et al (2016) found 21% explained variance of user behavior based on 162 and 74 empirical studies. Alam et al (2020) applied the UTAUT to explore the antecedents of intention to use AI in recruiting. In their study with 226 HR professionals in Bangladesh, they report 36% of explained variance in intention to use AI and 21% of explained variance in the actual use of AI in recruitment.…”
Section: Existing Approaches and Theories Regarding Technology Acceptancementioning
confidence: 99%
“…In this study, the researchers followed the quantitative research paradigm. The study used PLS-SEM to analyze the data and to evaluate the measurement and structural model to ensure the reliability and validity of the results (Alam, Dhar & Munira, 2020;Hair, Matthews, Matthews & Sarstedt, 2017;Hair Jr, Risher, Sarstedt & Ringle, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The UTAUT model consists of eight old technology acceptance models, namely the technology acceptance model (TAM), the theory of reasoned action, the theory of planned behavior (TPB), the motivation model, combined TAM and TPB, the innovation diffusion theory, the model of PC utilization, and social cognitive theory (Alghazi, Kamsin, Almaiah, Wong, & Shuib, 2021). Alghazi, Wong, Kamsin, Yadegaridehkordi, and Shuib (2020) conducted a literature review paper by collecting data on technology acceptance models from 2010 to 2020, remarking that UTAUT was the most widely used technology acceptance model, able to explain up to 70% of the variance, whereas other technology acceptance theories could only explain up to 53% concerning to behavioral intention (Alam, Dhar, & Munira, 2020;Wei, Luh, Huang, & Chang, 2021). In addition, the model can explain both the human and social factors that influence the intention to use and the actual use of technologies by giving a holistic view of understanding and replacing the eight fragmented theories.…”
Section: Theoretical Background Of the Studymentioning
confidence: 99%